2015
DOI: 10.2147/ott.s76484
|View full text |Cite
|
Sign up to set email alerts
|

Micro-ribonucleic acid 29b inhibits cell proliferation and invasion and enhances cell apoptosis and chemotherapy effects of cisplatin via targeting of DNMT3b and AKT3 in prostate cancer

Abstract: BackgroundMicro-ribonucleic acids (miRNAs) are crucial regulators in malignant tumors. miRNA-29b (miR-29b) has been identified as a tumor suppressor in prostate cancer (PCa). However, very few studies have investigated the effects of miR-29b in PCa, especially the mechanism and its association with chemotherapy. Our study aimed to explore the role and mechanism of miR-29b in PCa.Materials and methodsThe expression levels of miR-29b were detected in ten clinical PCa specimens and four different PCa cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
(60 reference statements)
2
29
0
Order By: Relevance
“…MicroRNA 29b (miR-29b) is a direct regulator of DNMT3B expression [40,41]. We assessed the expression of miR-29b in LX-2 cells with or without adiponectin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNA 29b (miR-29b) is a direct regulator of DNMT3B expression [40,41]. We assessed the expression of miR-29b in LX-2 cells with or without adiponectin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that miRNAs are dysregulated in many cancers and they play crucial roles in regulating a wide variety of biological processes such as cell death, metastasis, cell proliferation and chemosensitivity 913. In a study carried out by a group of researchers to analyze miRNA expression profiles across multiple cancers using data sets obtained from The Cancer Genome Atlas (TCGA), miR-629 was found to be upregulated in various cancers, such as bladder, head and neck, lung, kidney, breast and uterine cancer 14.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is downregulated in PCa cells as compared to normal tissues, and in particular in the androgen-independent cell line (LNCaP-AI) the expression of miR-29b was lower than LNCaP, namely the androgen-dependent cell line. Moreover, the expression of miR-29b inhibited cell invasion as well as cell proliferation, with a consequent apoptosis [153]. Ding et al observed that the miR-204 acts as a tumor suppressor in LNCaP and 22Rv1 cells and as oncomiR in PC-3 and CL1.…”
Section: Mirnas As Therapeutic Tool In Prostate Cancermentioning
confidence: 99%